Higher Order Thinking Skills (HOTS) in the Evaluation Instruments of Civics Education Text Book - Saraswati, Destriana; Fiaji, Noveria Anggraeni; Zulvarina, Prima; Yati binti Kamaruddin, Azni (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2025)
The implementation of Higher Order Thinking Skills (HOTS) in higher education learning materials has become increasingly crucial in preparing students for complex real-world challenges. This study examines the HOTS components in the evaluation instruments of the 2016 Civics Education textbook published by the Directorate General of Higher Education, Research, and Technology. The research specifically focuses on analyzing thinking levels based on Bloom's taxonomy, including analyzing (C4), evaluating (C5), and creating (C6) capabilities. This descriptive qualitative research employed a systematic literature study method. The data collection involved comprehensive analysis of evaluation instruments from each chapter of the textbook, using predetermined HOTS criteria and indicators. The analysis process included content analysis, categorization, and verification of thinking skill levels. The findings reveal varied distribution of HOTS components in the evaluation instruments: critical thinking (35.6%), creative thinking (11.8%), problem-solving (28.7%), and decision-making (25.3%). Furthermore, the analysis of thinking levels showed the following distribution: C4 (41.4%), C5 (19.5%), and C6 (38%). These results indicate a need for more balanced distribution of HOTS components, particularly in strengthening creative thinking and evaluative abilities in the textbook's evaluation instruments.